A zinc finger protein gene TksC3H20 positively regulates salt tolerance in Taraxacum kok-saghyz under salinity - Ran Wan; Boxuan Yuan; Fengyan Fang; Wenhao Wu; Shuangxian Liu; Yuxin Li; Xiaoyou Wu; Wei Li; Shugang Hui; Xuchu Wang (Plant Science, 2026)

Bilayer membrane with asymmetric wettability based on superhydrophilic/underwater superoleophobic cotton fabric for simultaneous oil-dye-water separation - Luwen Zhao; Yu Xia; Zhi Zhang; Yuan Zhu; Mingzhu Li; Jinlin Shen; Boxuan Zhu; Li Lv; Hongliang Ke; Zaisheng Cai; Yaping Zhao (Journal of Environmental Chemical Engineering, 2026)

Coordination-tailored high-spin Fe-MOF membrane electrode ensures selective singlet oxygen electrosynthesis: Non-radical emerging contaminants removal - Jian Sun; Shaofeng Li; Lijun Zhu; Boyang Meng; Boxuan Yang; Huan Wang; Tongzhou Liu (Water Research, 2026)

A robust nonlinear model-based controller design for a hybrid wave compensation boarding platform for offshore wind farm operation and maintenance - Boxuan Chen; Lei Tan; Peng Li; Lun Tan; Hongbo Wang; Chaohe Chen (Ocean Engineering, 2026)

Prediction of breakthrough time in hydrogen purification from coke oven gas using deep learning model - Yuqi Zhang; Boxuan Zhang; Zhibin Liu; Leiming Xiong; Yanchuan Cheng; Minke Huang; Cheng Lu; Hengcong Tao; Jingfa Li; Ziming Hu; Bohong Wang; Yue Su (Journal of Cleaner Production, 2026)

Construction and validation of a fast selective catalytic reduction (SCR) strategy for enhancing low-temperature activity of zeolite catalysts under microwave irradiation - Xiangru Li; Yun Chen; Xuehong Zi; Jinyu Yuan; Yao Cheng; Xiaoqian Cheng; Kaiyu Hu; Boxuan Song; Wenjun Liang; Liyun Song (Journal of Environmental Chemical Engineering, 2026)

Long-term organic amendments regulate cbbL-harboring bacterial community via soil physicochemical properties and enzyme activities in a paddy soil - Jiangbing Xu; Boxuan Li; Yuhao Wu; Lei Liu; Guoyi Zhou; Xiaoli Liu; Ling Chen; Meng Wu; Xiaoyan Ma; Catherine Preece; Daming Li; Ming Liu (Journal of Soils and Sediments, 2026)

Construction of recombinant OPIV3 virus vectoring bivalent Mycoplasma ovipneumoniae adhesins - Xu Zhang; Yijia Liu; Boxuan Yin; Changyan Li; Miao sun; Qinghong Xue; Jinhai Huang (Archives of Virology, 2026)

Impact of equivalence ratio on soot emissions from turbofan combustor during takeoff and ground idle status - Guangze Li; Zhenzhong Zhang; Liuyong Chang; Ragui Karim; Yiwei Zhao; Boxuan Cui; Longfei Chen; Ye Kang; Lei He (Journal of Aerosol Science, 2026)

Zero-solvent-emission rapid synthesis of aerogel beads: A food-colorant adsorbent with biocompatibility and facile separation - Boxuan Peng; Jiahui Li; Tong Wu; Shiyi Wang; Fangzheng Zhao; Chunyue Zhao; Qingyun Liu; Enchang Liu; Huizhen Han; Siyuan Yu; Jinfeng Xing (Chemical Engineering Journal, 2026)

Unpaved road-altered confluence networks exacerbate soil organic carbon loss in mountainous forested catchments - Zaihui Yu; Qinghe Zhao; Shengyan Ding; Jinhai Yu; Boxuan Liu; Wanfu Feng; Yuefeng Li; Jiliang Zhou (Journal of Hydrology, 2026)

The influence of Ag modification strategies on NH3-SCO performance of Cu-SSZ-13 catalysts - Mengyi Kou; Guizhen Zhang; Liyun Song; Shuzhen Li; Yao Cheng; Xiaoqian Cheng; Boxuan Song; Hong He; Zhenguo Li (Chemical Engineering Journal, 2026)

Soil moisture variability of typical mixed forests in the north-south climatic transitional zone of China - Yu Mei; Qinghe Zhao; Peikun Li; Xiaojian Qin; Boxuan Liu; Zhize Li; Tingting Wang; Shengyan Ding (Journal of Environmental Management, 2025)

Electrochemical behaviors and exothermal analyses of commercial NCM lithium-ion batteries during overdischarge - Lun Li; Boxuan Wang; Zhizuan Zhou; Junhui Gong; Lizhong Yang (Process Safety and Environmental Protection, 2025)

Responses in roots of Sesuvium portulacastrum to copper stress: Joint regulation of antioxidant system-copper chelation and transport-metabolic coordination - Zhaozhen Xiang; Boxuan Yuan; Yang Yang; Fengyan Fang; Minmin He; Yuxin Li; Shugang Hui; Xuchu Wang (Plant Science, 2025)

Morphological and nanostructural characteristics of aircraft-emitted soot particles during taxiing condition: A comparative study based on TAPS combustor - Liuyong Chang; Jie Ji; Longfei Chen; Haiquan Wu; Xinyu Wang; Boxuan Cui; Jing Wang; Guangze Li; Ye Kang; Lei He (Environmental Pollution, 2025)

Cationic liposome-mediated scavenging of cell-free DNA: An innovative and alternative therapeutic approach for efficient treatment of dry eye disease - Juan Wang; Jialuo Zhang; Shujing Liu; Jing Tang; Jiajun Liu; Ying Huang; Huazhang Zeng; Hu Yang; Boxuan Li (Chemical Engineering Journal, 2025)

Multi-omics insights into 6PPD- and 6PPDQ-induced gut-liver axis disruption and non-alcoholic fatty liver disease progression in zebrafish (Danio rerio) - Yu Feng; Hongyi Xian; Ruobing Bai; Zhiming Li; Hao Li; Long Zhang; Xiyun Huang; Yuji Huang; Boxuan Liang; Yanhong Deng; Xiaohong Yang; Xiaoqing Chen; et al. (Journal of Hazardous Materials, 2025)

A Point Cloud Generation Network for Automatic Prediction of Postoperative Maxillofacial Soft Tissue - Ruiyang Li; Bimeng Jie; Boxuan Han; Yuchao Zheng; Chengyi Wang; Xuan Yang; Yi Zhang; Hongen Liao; Yang He; Longfei Ma (Annals of Biomedical Engineering, 2025)

An experimental study on pedestrian walking speed considering combined effect of heeling and trim - Yong Jiang; Zihang Li; Yurou Mao; Boxuan Wang; Dawei Zhang (Ocean Engineering, 2025)

NiFe-LDH modified biochar enhances peroxymonosulfate activation system: Mechanism for singlet oxygen (1O2) generation and tetracycline degradation - Jingyang Li; Yuexiang Li; Xue Ye; Yunze Ruan; Boxuan Yang; Fanrong Pan; Zhiliang Chen; Shanshuai Chen; Xin Jin (Journal of Environmental Chemical Engineering, 2025)

A starch-like polysaccharide isolated from Hirsutella sinensis mycelia alleviates DSS-induced colitis in mice by strengthening the intestinal barrier, maintaining immune homeostasis, and modulating the gut microbiota and SCFA metabolism - Yu Li; Hailiang Wang; Hongtao Bi; Jingyue Feng; Tingting Gao; Dai Dong; Guoqiang Li; Boxuan Liu; Hongyan Yuan; Weihua Ni (Food Bioscience, 2025)

Genome-wide analysis of ascorbate peroxidase and functional characterization of SpAPX249b and SpAPX285c for salt tolerance in Sesuvium portulacastrum L. - Houli Zhou; Yuxin Li; Boxuan Yuan; Qinqin Nie; Zhaozhen Xiang; Lixia He; Yongfei Wang; Zhanchao Yang; Juanying Wang; Shugang Hui; Xuchu Wang (Plant Cell Reports, 2025)

Emission characteristics, environmental impacts and health risk assessment of volatile organic compounds from the typical chemical industry in China - Kaitao Chen; Xin Gu; Min Cai; Weicheng Zhao; Boxuan Wang; Haoran Yang; Xingang Liu; Xingru Li (Journal of Environmental Sciences, 2025)

Thiophene and acetylene functionalized conjugated organic polymers with hollow nanotube structure toward high-performance photocatalytic H2O2 production - Yuntong Li; Boxuan Ding; Yan Sui; Wentong Chen; Dongsheng Liu; Wei Huang; Xiaodan Li; Wei Wang; Hong Zhong; Cheng Liu (Journal of Environmental Chemical Engineering, 2025)

The influence of pH on the liquid-phase transformation of phenolic compounds driven by nitrite photolysis: Implications for characteristics, products and cytotoxicity - Yiran Wang; Min Cai; Yuchen Wang; Weicheng Zhao; Boxuan Wang; Gehui Wang; Xingru Li (Science of The Total Environment, 2024)

Triple-crosslinked double-network alginate/dextran/dendrimer hydrogel with tunable mechanical and adhesive properties: A potential candidate for sutureless keratoplasty - Wen Zhang; Shujing Liu; Lixiang Wang; Boxuan Li; Mengzhen Xie; Yingping Deng; Jialuo Zhang; Huazhang Zeng; Li Qiu; Lisha Huang; Tao Gou; Xiaobo Cen; et al. (Carbohydrate Polymers, 2024)

Intertwined role of mechanism identification by DFT-XAFS and engineering considerations in the evolution of P adsorbents - Ruining Zhao; Benhang Li; Siyuan Chen; Boxuan Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Science of The Total Environment, 2024)

21Ne and 10Be dating of folded fluvial terraces: Constraining active deformation of the Guman fold along the foothill of the western Kunlun mountains (Xinjiang, China) - Jianhong Xu; Jie Chen; Tao Li; Boxuan Zhang; Ning Di; Wei Pang (Journal of Structural Geology, 2024)

Microplastic co-exposure elevates cadmium accumulation in mouse tissue after rice consumption: Mechanisms and health implications - Shan Chen; Haijun Gan; Xinying Lin; Boxuan Wang; Mengya Li; Lena Q. Ma; Dongmei Zhou; Hongbo Li (Journal of Hazardous Materials, 2024)

Simultaneous nitrification and denitrification in a hybrid activated sludge-membrane aerated biofilm reactor (H-MABR) for nitrogen removal from low COD/N interflow: A pilot-scale study - Hengyi Liu; Lei Li; Wenjie Ye; Boxuan Zhao; Yun Peng; Guotao Liu; Xiaofeng Gao; Xuya Peng (Journal of Environmental Management, 2024)

Rapid Rescue of Goose Astrovirus Genome via Red/ET Assembly - Daqing Cui; Shujun Li; Boxuan Yin; Changyan Li; Lilin Zhang; Zexing Li; Jinhai Huang (Food and Environmental Virology, 2024)

Natural mineral and industrial solid waste-based adsorbent for perfluorooctanoic acid and perfluorooctane sulfonate removal from surface water: Advances and prospects - Siyuan Chen; Benhang Li; Ruining Zhao; Boxuan Zhang; Yuqing Zhang; Jiale Chen; Jiahe Sun; Xiaodong Ma (Chemosphere, 2024)

Impacts and influencing pathways of urbanization on carbon–water-energy-food nexus across Chinese cities - Chenggang Li; Yong Liu; Zhenci Xu; Gang Zhao; Youhui Bao; Chengcheng Cai; Yu Lu; Yufeng Mao; Alexander Boxuan Wang; Liang Wu (Environment, Development and Sustainability, 2024)
Food, water, energy and carbon (F-W-E-C), as important factors of urban development, have synergistic effects and trade-off effects with each other. Scientifically assessing the impact of urbanization on the F-W-E-C nexus is beneficial to optimize the urban development layout and achieve the sustainable urban development. Nevertheless, extant studies have not evaluated the impact and influencing pathways of urbanization on the F-W-E-C nexus. In this study, the Coupling Coordination Degree Model is used to explore the F-W-E-C nexus of 252 prefecture-level cities in China. The panel data model and mediating effect model are utilized to study the impact of urbanization on the F-W-E-C nexus and the impact pathways. This study finds that the F-W-E-C nexus across Chinese cities is weak trade-off. The urbanization promotes the synergy of F-W-E-C. The positive impact is greater in the central cities than in the eastern and western cities, and is greater in medium-sized cities than in small cities, large cities and above. The technological progress is an important pathway of urbanization impacting the F-W-E-C nexus, and assists urbanization to generate a positive influence on the F-W-E-C nexus. This research has implications for promoting a systematic, orderly, and rational coordination development of F-W-E-C and for sustainable urbanization development in China and the world.

Gender-specific effects of polystyrene nanoplastic exposure on triclosan-induced reproductive toxicity in zebrafish (Danio rerio) - Zhiming Li; Hongyi Xian; Rongyi Ye; Yizhou Zhong; Boxuan Liang; Yuji Huang; Mingzhu Dai; Jie Guo; Shuqin Tang; Xiaohu Ren; Ruobing Bai; Yu Feng; et al. (Science of The Total Environment, 2024)

From cradle to grave: Deciphering sex-specific disruptions of the nervous and reproductive systems through interactions of 4-methylbenzylidene camphor and nanoplastics in adult zebrafish - Hongyi Xian; Zhiming Li; Ruobing Bai; Rongyi Ye; Yu Feng; Yizhou Zhong; Boxuan Liang; Yuji Huang; Jie Guo; Binjie Wang; Mingzhu Dai; Shuqin Tang; et al. (Journal of Hazardous Materials, 2024)

Cost-effectiveness of latent tuberculosis infection testing and treatment with 6-week regimen among key population in rural communities in China: a decision analysis study - Xuefang Cao; Tonglei Guo; Henan Xin; Jiang Du; Chenlu Yang; Boxuan Feng; Yijun He; Lingyu Shen; Yuanzhi Di; Zihan Li; Yanxiao Chen; Jianguo Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Revealing new insights: Two-center evidence of microplastics in human vitreous humor and their implications for ocular health - Yizhou Zhong; Yuhang Yang; Linan Zhang; Dahui Ma; Kailiang Wen; Jiachun Cai; Zhanmou Cai; Cui Wang; Xiaoyan Chai; Jingwen Zhong; Boxuan Liang; Yuji Huang; et al. (Science of The Total Environment, 2024)

Vertically designed high-performance and flexible thermoelectric generator based on optimized PEDOT:PSS/SWCNTs composite films - Binjie Xia; Xiao-Lei Shi; Li Zhang; Jia Luo; Wen-Yi Chen; Boxuan Hu; Tianyi Cao; Ting Wu; Wei-Di Liu; Yanling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Seasonal variations of microplastics in surface water and sediment in an inland river drinking water source in southern China - Wenyu Zhao; Jing Li; Mengyue Liu; Rui Wang; Boxuan Zhang; Xiang-Zhou Meng; Shengwei Zhang (Science of The Total Environment, 2024)

Emerging and legacy perfluoroalkyl and polyfluoroalkyl substances (PFAS) in surface water around three international airports in China - Jing Liu; Zhen Zhao; Jie Li; Xia Hua; Boxuan Zhang; Caijun Tang; Xinyi An; Tian Lin (Chemosphere, 2023)

Solvothermally silver doping boosting the thermoelectric performance of polycrystalline Bi2Te3 - Wen-Yi Chen; Xiao-Lei Shi; Qishuo Yang; Meng Li; Wanyu Lyu; Ting Liu; Tianyi Cao; Boxuan Hu; Weidi Liu; Shuai Sun; Yuanqing Mao; Matthew Dargusch; et al. (Chemical Engineering Journal, 2023)

Secondary metal doped cuprous-cyanoimidazole frameworks for triple-mode detection of dopamine - Hua Wei; Jian Liu; Xin Wang; Zihan Li; Lijuan Ju; Boxuan Yao; Jiarui Zhou; Lei Zhao; Mingyang Zhou; Jie Zhang; Shenghong Yang (Analytica Chimica Acta, 2023)

Impact of food matrices on the characteristics and cellular toxicities of ingested nanoplastics in a simulated digestive tract - Zhiming Li; Yuji Huang; Yizhou Zhong; Boxuan Liang; Xingfen Yang; Qing Wang; Haixia Sui; Zhenlie Huang (Food and Chemical Toxicology, 2023)

Design and Field Test of a Remotely Controlled Self-propelled Potato Harvester with Manual Sorting Platform - Boxuan Jia; Wei Sun; Zhiwei Zhao; Hucun Wang; Hua Zhang; Xiaolong Liu; Hui Li (American Journal of Potato Research, 2023)

CircBCL11B acts as a ceRNA to facilitate 1,2-dichloroethane-induced astrocyte swelling via miR-29b-3p/AQP4 axis in SVG p12 cells - Yizhou Zhong; Bingli Zhang; Yuji Huang; Jiaxin Du; Boxuan Liang; Zhiming Li; Rongyi Ye; Bo Wang; Hongyi Xian; Xifei Yang; Weifeng Rong; Xiang Guo; et al. (Toxicology Letters, 2023)

Stabilization mechanism of Pb with an amino- and mercapto-polymer to assist phytoremediation - Feili Li; Boxuan Yang; Feng Yang; Jiahao Wu; Jing Chen; Shuang Song; Jianhong Jia (Journal of Hazardous Materials, 2023)